Selecting a coastal cruise port of call location in mainland China using the AHP method - Yuanyuan Zhu; Juehao Cheng (Journal of Shipping and Trade (JST), 2020)
Increasing needs of mass tourism give the cruise industry opportunity to booming rapidly. The remarkable contribution of the cruise industry makes the port cities incorporate cruise tourism into development strategy. Whether a cruise port was included in the cruise lines' itineraries design will directly affect the profitability and survival of the port. As the contribution to cruise ports and hinterland cities, it is necessary to analyze the factors that affect the selection of cruise ports and design of itineraries. In contrast to ocean cruising, the coastal cruise market is rarely addressed in the academic literature. Particularly, there is a substantial gap regarding the changes taking place in the China coastal cruise market, and this paper seeks to address this issue. To respond to the need of cruise liners and passengers more accurately, this paper aims to identify the main issues affecting the coastal cruise port of call process exactly, reasonable and scientifically. And build a fruitful partnership relation between ports and cruise companies so that to provide valuable information for cruise lines and destinations to develop continuous attracting cruise tourism offerings as well as improve marketing communications, thereby make contribution to the port and regional economy. Valuable information for cruise lines and destinations to develop continuous attracting cruise tourism offerings as well as improve marketing communications, thereby make contribution to the cruise economy.
Keywords: 650; Coastal cruise tourism; Cruise port selection; AHP (analytic hierarchy process); Cruise industry; Cruise port competitiveness comparison; Port management